2023
DOI: 10.3390/clinpract13030054
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Anxiety, and Depression Levels among University Students: Three Years from the Beginning of the Pandemic

Abstract: Background: Three years after the outbreak of the COVID-19 pandemic, psychological distress among college students remains increased. This study assesses stress, anxiety, and depression levels among students of the Aristotle University of Thessaloniki by the end of the third year of the pandemic (November 2022), revealing demographic characteristics and probable stressors. Methods: A questionnaire was distributed in November 2022 via the academic students’ e-mails. The evaluation was performed with the DASS21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…In our study, female participants exhibited higher levels of stress and anxiety symptoms relative to male participants. This finding coincides with several earlier studies [ 32 , 33 ], which also observed higher rates of stress and anxiety among women. This may be attributed to the biological, hormonal, and psychosocial differences between males and females [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, female participants exhibited higher levels of stress and anxiety symptoms relative to male participants. This finding coincides with several earlier studies [ 32 , 33 ], which also observed higher rates of stress and anxiety among women. This may be attributed to the biological, hormonal, and psychosocial differences between males and females [ 34 ].…”
Section: Discussionsupporting
confidence: 93%